Citrus maxima (Burm.) Merr. fruit juice and peel extract mediated synthesis of silver nanoparticles (AgNPs) and their applications as antimicrobial agents and plant growth enhancers: DOI: 10.48129/kjs.19889 - Das, Indukalpa; Sonowal, Abhijit; Gogoi, Bhaskarjyoti; Sharma, Bidisha; Patowary, Kaustuvmani; Borah, Debajit (Kuwait Journal of Science, 2022)
Green synthesis of metal nanoparticles (NP) has emerged as a recent trend in green chemistry. However, their potential in the field of agriculture is yet underexplored. In this study, silver nanoparticles (Ag NPs) were synthesized by using the fruit juice and peel extract of Citrus maxima (Burm.) Merr. as a reducing and capping agent. The nano-primed seeds of Zea mays, Glycine max, and Cicer arietinum showed enhanced germination rate up to 90% as compared to the respective control (30-60%) and also enhanced plant growth. The HRTEM images Ag NPs showed well dispersed NPs with an average size range of 10-20 nm. The XRD spectra confirmed the crystalline nature of Ag NPs with fcc lattice points of 101, 111, 200, 220, and 311. The FTIR spectra confirm the presence of ʋC=C-H, ʋCH2, ʋC=O (stretch), ʋC=C (stretch), ʋC-H (bend), ʋC-O (bend) in the Ag NPs synthesized by the fruit and peel extract. The Ag NPs also showed potential antimicrobial effects against both Gram-positive (Staphylococcus aureus) and negative bacteria (Klebsiella pneumonia).